EXPERIENCE OF THE SACRED MONTH IN QS. AT- TAUBAH [9]: 36: STUDY OF THE LIVING QUR'AN IN PAYABAKUNG, HAMPARAN PERAK - Arya Handika Pransetia; Adenan (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2026)
This study examines community practices regarding the sacred months described in QS. At-Taubah [9]: 36 in Payabakung Village, Hamparan Perak, through a Living Qur’an perspective. The research was motivated by the limited empirical studies that connect Qur’anic teachings on the sacred months with local religious practices. This study aims to analyze the community’s understanding, forms of practice, and internalization of Qur’anic values during the sacred months. A qualitative method was employed using observation, in-depth interviews, and documentation. Informants were selected purposively, including religious leaders, community leaders, village officials, and residents involved in religious activities. The findings show that the sacred months are understood as honored times that encourage increased worship, moral self-control, charity, Qur’anic recitation, religious gatherings, and social solidarity. These practices appear in Dzulqa’dah, Dzulhijjah, Muharram, and Rajab through collective and individual religious activities. The study concludes that QS. At-Taubah [9]: 36 is not only understood textually but is also lived through social-religious practices that strengthen spirituality, morality, and community cohesion.